Paul Celan La poesia come frontiera filosofica - Baldi, Massimo; Desideri, Fabrizio (Studi e saggi, 2008)
Poetry as a "philosophical frontier" is the concept focused in this book on the poetry of Paul Celan. It is not precipitate to consider that the peculiarity of Celan's poetry and its reception lies in the persistent and ongoing interest displayed by philosophical criticism. Adopting an inclusive formula that goes beyond the mere notion of a "philosophical space", Massimo Baldi and Fabrizio Desideri aim to bring together readings and interpretative theories that are significantly diverse, albeit marked by the common intention of focusing the radical singularity of Celan's writing. All the essays presented here effectively reveal an attention to that engagement inherent in the letter of the poetic dictate, in the pungency of its inscription, which we must respect and listen to if we wish to understand Celan.